Modulation of thalamic network connectivity using transcranial direct current stimulation based on resting-state functional magnetic resonance imaging to improve hypoxia-induced cognitive impairments - Dalong, Guo; Yufei, Qin; Lei, Yang; Pengfei, Li; Anqi, Ye; Zichuan, Guo; Cong, Wang; Yubin, Zhou (Frontiers in Neuroscience, 2022)
Hypoxic conditions at high altitudes severely affect cognitive functions such as vigilance, attention, and memory and reduce cognitive ability. Hence, there is a critical need to investigate methods and associated mechanisms for improving the cognitive ability of workers at high altitudes. This study aimed to use transcranial direct current stimulation (tDCS) to modulate thalamic network functional connectivity to enhance cognitive ability. We recruited 20 healthy participants that underwent hypoxia exposure in a hypoxic chamber at atmospheric pressure to simulate a hypoxic environment at 4,000 m. Participants received both sham and real stimulation. tDCS significantly improved the participants’ emotional status, including depression, fatigue, and energy level. These effects were sustained for more than 6 hours (P<0.05 at the second to fifth measurements). In addition, tDCS enhanced vigilance, but this was only effective within 2 hours (P<0.05 at the second and third measurements). Central fatigue was significantly ameliorated, and cerebral blood oxygen saturation was increased within 4 hours (P<0.05 at the second, third, and fourth measurements). Furthermore, functional connectivity results using the thalamus as a seed revealed enhanced connectivity between the thalamus and hippocampus, cingulate gyrus, and amygdala after tDCS. These results indicated that tDCS increased local cerebral blood oxygen saturation and enhanced thalamic network connectivity in a hypoxic environment, thereby improving vigilance, depression, fatigue, and energy levels. These findings suggest that tDCS may partially rescue the cognitive decline caused by hypoxia within a short period. This approach affords a safe and effective cognitive enhancement method for all types of high-altitude workers with a large mental load.